UPAYA ASĀTĪDZ DALAM MENINGKATKAN KEMAMPUAN MEMBACA KITAB KUNING AL-YAQŪT AL-NAFĪS DI MADRASAH ALIYAH - Atna Akhiryani; Titin Fatimah; ASLAN F LATINGARA (Albariq: Jurnal Pendidikan Bahasa Arab, 2021)
This research aims at finding out the teachers’ effort in developing the students’ ability in reading Al-Yaqūt Al-Nafīs at class two senior high school. This research employed the Descriptive Qualitative method. Its findings indicate an increase in the teachers’ effort in developing students’ ability in reading and translating Al-Yaqūt Al-Nafīs. The teachers applied sorogan method in the teaching and learning process and applied repetition and practice techniques in learning Al-Yaqūt Al-Nafīs.